Inoculation reduces social media engagement with affectively polarized content in the UK and US - Fintan Smith; Almog Simchon; Dawn Holford; Stephan Lewandowsky (Communications Psychology)
Abstract The generation and distribution of hyper-partisan content on social media has gained millions of exposure across platforms, often allowing malevolent actors to influence and disrupt democracies. The spread of this content is facilitated by real users’ engaging with it on platforms. The current study tests the efficacy of an ‘inoculation’ intervention via six online survey-based experiments in the UK and US. Experiments 1–3 (total N = 3276) found that the inoculation significantly reduced self-reported engagement with polarising stimuli. However, Experiments 4–6 (total N = 1878) found no effects on participants’ self-produced written text discussing the topic. The implications of these findings are discussed in the context of the literature on polarisation and previous interventions to reduce engagement with disinformation.